Effects of Erythropoietin on Glucose Metabolism - Mikolás, E.; Cseh, J.; Pap, M.; Szijárto, I. A.; Balogh, A.; Laczy, B.; Bekő, V.; Fisi, V.; Molnár, G. A.; Mérei, Á.; Szeberényi, J.; Wittmann, I. (Hormone and Metabolic Research, 2012)
We purposed to determine the impact of erythropoietin on altering glucose metabolism in the settings of in vitro and in vivo experiments. The acute effect of erythropoietin on lowering blood glucose levels was studied in animal experiments. In [3H]-deoxy-d-glucose isotope studies we measured glucose uptake with insulin and erythropoietin using 3T3-L1 cells cultured under normal or high glucose conditions. Altered activation of Akt and ERK pathways was evaluated in immunoblot analyses. Immunocytochemistry was conducted to determine the glucose transporter 4 translocation to the plasma membrane. Addition of erythropoietin significantly lowered blood glucose levels in vivo in rats. The glucose uptake was markedly increased by erythropoietin treatment (at concentrations 0.15, 0.3, and 0.625 ng/ml) in adipocytes grown in high glucose medium (p<0.05), but it remained unaltered in cells under normal glucose conditions. Significant increase of phosphorylation of ERK and Akt was detected due to erythropoietin (p<0.05). Co-administration of erythropoietin and insulin resulted in higher phosphorylation of Akt and [3H]-deoxy-d-glucose uptake in adipocytes than insulin treatment alone. We found that erythropoietin induced the trafficking of glucose transporter 4 to the plasma membrane. Our data showed that erythropoietin significantly decreased blood glucose levels both in vivo and in vitro, in part, by increasing glucose uptake via the activation of Akt pathway. Preliminary data revealed that adipocytes most likely exhibit a specific receptor for erythropoietin.
Keywords: diabetes mellitus type 1; diabetes mellitus type 2; fat cell; insulin